2013
DOI: 10.1111/ntwe.12000
|View full text |Cite
|
Sign up to set email alerts
|

‘You monitor performance at every hour’: labour and the management of performance in the supermarket supply chain

Abstract: With reference to the performance management research agenda, this article focuses on the politics of production in food manufacturing and distribution companies in the supermarket supply chain. Burawoy's concept of 'factory regimes' is utilised to explore the broader context of labour process change in interlinked organisations in the retail supply chain. The article examines the extent to which new despotic or coercive regime characteristics are emerging that weakens the power of both suppliers and labour. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
53
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(54 citation statements)
references
References 18 publications
0
53
0
Order By: Relevance
“…This approach was widely criticized by labour process theorists (e.g. Braverman, 1974;Thompson and Smith, 2010;Newsome et al, 2013). Labour process theory focuses on labour power's ongoing transformations in the context of capitalism (Thompson and Smith, 2010) and is committed to identifying how the 'qualitative intensification of labour' seen in emotional, affective and aesthetic labour impacts working lives and the capturing of employees' tacit knowledge (Thompson, 2010).…”
Section: Thinking About Quantificationmentioning
confidence: 99%
“…This approach was widely criticized by labour process theorists (e.g. Braverman, 1974;Thompson and Smith, 2010;Newsome et al, 2013). Labour process theory focuses on labour power's ongoing transformations in the context of capitalism (Thompson and Smith, 2010) and is committed to identifying how the 'qualitative intensification of labour' seen in emotional, affective and aesthetic labour impacts working lives and the capturing of employees' tacit knowledge (Thompson, 2010).…”
Section: Thinking About Quantificationmentioning
confidence: 99%
“…The Newsome et al . (; see also Newsome, ) research on UK retailer supply chains showed that in order to meet the demands of their clients, suppliers adopted new technology to monitor labour performance and speed up work processes. Similarly, Pulignano () revealed in her study of supply chains in the Italian automobile industry that the management in supplier firms used supply chain pressure as a mechanism to tighten their control of their labour process.…”
Section: Supply Chain Pressure and Employment Practicesmentioning
confidence: 99%
“…Critically, despite the continued shift of responsibility for conflict management from HR to the line (McGovern et al, 1997;Teague and Roche, 2012), this concern has received little further consideration as the policy agenda has developed. Furthermore, it could be argued that the traditional preference of managers for informality (Rollinson et al, 1996) may sit uneasily beside increased emphasis on more systematic performance management (Taylor, et al, 2010;Newsome et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…This includes appraisal and performance review practices as part of a developmental approach, but also involves the management of poor performance (Dunn and Wilkinson, 2002;Newsome et al, 2013) through the application of absence and capability procedures. Although these are also now more explicitly linked to disciplinary outcomes, managers are encouraged to act in a 'flexible and positive way' (Armstrong and Barron 2005, p.12) and there appears to be an emphasis on the benefits of informality as a way of building consensus and enhancing performance in the context of employee involvement for example (Marchington and Suter, 2013).…”
mentioning
confidence: 99%